2018
DOI: 10.1111/1750-3841.14340
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Volatile Compounds and Sensory Analysis of Jasmine Scented Black Tea Produced by Different Scenting Processes

Abstract: Jasmine scented black tea is widely popular in China and the scenting process is the most crucial issue affecting its aroma quality. This study aimed to analyze the influence of different processes on aroma quality and the specific contribution of volatiles to aroma quality. To achieve it, the headspace solid‐phase microextraction method combined with gas‐chromatography mass‐spectrometry was used to identify and quantify the volatile compounds, and further collected the characteristics according to odor activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 29 publications
1
41
0
1
Order By: Relevance
“…Linalool, imparts a floral, fruity, and woody odor in jasmine tea, and benzyl alcohol provides a sweet, roasted, mild, fruity and citrus-like aroma, were contained in both the tea dhool and jasmine flowers [4,27,31]. Here, the relative content of 3-hexen-1-ol in alcohols was lower than both linalool and benzyl alcohol.…”
Section: Alcoholsmentioning
confidence: 88%
See 4 more Smart Citations
“…Linalool, imparts a floral, fruity, and woody odor in jasmine tea, and benzyl alcohol provides a sweet, roasted, mild, fruity and citrus-like aroma, were contained in both the tea dhool and jasmine flowers [4,27,31]. Here, the relative content of 3-hexen-1-ol in alcohols was lower than both linalool and benzyl alcohol.…”
Section: Alcoholsmentioning
confidence: 88%
“…These four volatile compounds are found in green tea, and existing studies show that cyclopentanone, (Z)-Linalool oxide and (E)-Linalool oxide are negatively correlated with the grade of green tea [16,32]. It also was reported that phenyl ethyl alcohol, α-Terpineol, and geraniol were all derived from jasmine flowers, having floral or sweet odor [3,4,33]. MS,RI Eugenol 0.12 ± 0.00b 0.25 ± 0.04a 0.11 ± 0.02b 0.10 ± 0.03b 0.05 ± 0.02b 0.06 ± 0.02b a-d Means ± SD followed by the same letter, within a row, are not significantly different (p > 0.05); e 1G, 2G, 3G, 4G, 5G, and 6G represent the standard sample for the grade of jasmine tea from high rank to low rank; f MI, method of identification; N.D., peak intensity lower than triple signal-to-noise.…”
Section: Alcoholsmentioning
confidence: 99%
See 3 more Smart Citations